SKRINING FITOKIMIA TERHADAP EKSTRAK ETANOL DAUN SURIAN (Toona sinensis Roem) - Andi Deffi Ramadani; Erwin Erwin; Ritbey Ruga (Jurusan Kimia FMIPA UNMUL, 2026)
Toona sinensis (Surian) is a species of the Toona genus of the Meliaceae family that is highly resistant to cold weather compared to other Meliaceae families. T. sinensis is widely used as a traditional medicine such as a worm medicine, dysentery, expectorant, as a tonic and can also be used to lower blood sugar and for the treatment of syphilis and many other benefits. Based on previous research, it is known that the content of secondary metabolites found in the surian plant includes limonoids, phytol, flavonoids, essential oils, phenol triterpenoids, and catechins. This study was conducted to obtain T. sinensis leaf extract through a maceration process using ethanol solvent, and phytochemical tests to determine the content of secondary metabolites in it. The extraction results obtained in the form of a dark green isolate, with a mass of 24.82 grams and a yield of 17.98%. Phytochemical testing showed that the ethanol extract of Surian leaves contains secondary metabolite compounds such as alkaloids, steroids, phenolics, and quinones.